(untitled) (Journal of Bio-Science, 2021)
The long whiskers catfish, Mystus gulio (Hamilton, 1822), is a valuable, delicious food fish in coastal areas of Bangladesh. It is found in fresh and brackish water of South Asian region. The present study illustrates the temporal variation of condition factor (KF) and prey-predator through relative weight (WR) along with length-weight relation (LWR) of M. gulio in the Maloncho River at southern Bangladesh. There were a total of 1200 individuals collected between January-December 2017 and October 2019 to June 2020. Different traditional gears (such as cast net, seine net, square lift net) were used for collecting the fish samples. There were 35% males and 65% females. The total length of fish ranged 7.8-18.3 cm for males and 9.3-22.1 cm for females. The body weight ranged 8.80–72.34 g for males and 8.09-128.82 g for females. LWR was significant with r2 value >0.950. The calculated co-efficient (b) were negative allometric growth in male and female (b<3.0, p<0.001). The KF indicated the best condition of this species. WR revealed no significant difference from 100 for both sex (p = 0.441) and females (p = 0.221), indicating a suitable habitat for growth. From conservation point of view, the findings of this present study on M. gulio will be helpful in Bangladesh (Maloncho River) and neighboring countries. J. Bio-Sci. 29(1): 111-122, 2021 (June)